2021
DOI: 10.3889/oamjms.2021.5888
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Barriers Regarding Health Research among Medical Students in Saudi Arabia

Abstract: BACKGROUND: Research is the basic component of health science curriculum. AIM: The objective of the study is to determine the knowledge, attitude, and barriers regarding health research among health science students. METHODS: It is a cross-sectional study and 294 study participants were selected through stratified random sampling from different health science colleges (medicine, dental, nursing, and applied science). A validated, structured, and pre-tested questionnaire was used. Knowledge and attitudes were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Other studies have also reported that the most common barriers to research are lack of proper mentoring from the faculty staff, Lack of reward and/or motivation, and lack of time due to overburden with educational activities. [17,19,20] It is essential to drive students to develop positive attitudes toward undergraduate research and resolve any barrier that may hinder medical students from productive engagement in undergraduate research activities. [22] Considering research experience in our study, overall 50.9% of the students self-reported that they did research during their undergraduate phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also reported that the most common barriers to research are lack of proper mentoring from the faculty staff, Lack of reward and/or motivation, and lack of time due to overburden with educational activities. [17,19,20] It is essential to drive students to develop positive attitudes toward undergraduate research and resolve any barrier that may hinder medical students from productive engagement in undergraduate research activities. [22] Considering research experience in our study, overall 50.9% of the students self-reported that they did research during their undergraduate phase.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported by previous studies from Saudi Arabia. [9,[17][18][19][20] Our study demonstrates that only 2.8% of the whole students recorded a good awareness level regarding research and 66.5% had a poor awareness level. The highest awareness level (good level) was recorded among nursing college students (6.9%) followed by pharmacy and medical college students (2.7% for each).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation